Exploring Information Systems/Technology Outsourcing in Saudi Organizations: An Empirical Study - Ahmad A. Abu-Musa (Journal of Accounting, Business and Management (JABM), 2011)
This research aims to identify the concept of outsourcing of systems Information Systems/Information Technology (IS/IT) and to empirically examine the main benefits and risks of domestic IS/IT outsourcing in Saudi enterprises. An empirical study using a self-administered questionnaire survey was carried out. Five hundred questionnaires were distributed to a random sample of Saudi organizations, where 160 valid completed questionnaires - representing 32% response rate - were collected and analyzed. The results of the study show that the majority of the Saudi organizations are using partial or total IS/IT outsourcing. Most Saudi organizations are pricing the IS/IT outsourcing services either on a cost based or a fixed lump sum price. The results also show that most Saudi enterprises own the data centers facilities, while a small number of organizations own the IT assets such as equipment and programs. Saudi organizations prefer best breed multiple suppliers rather than relying on one supplier to reduce the outsourcing risk. A high percentage of Saudi organizations are regionally outsourcing the development and maintenance of the software, hardware, and integrated information systems, as well as staff training and education. The findings suggest that the main advantages of IS/IT outsourcing in Saudi organizations are: enhancing organizations information technology (IT) competence, improving the original quality and efficiency of information services, increasing access to skilled IS/IT personnel and expertise, and reducing the risk of technological obsolescence. While the main risks of IS/IT outsourcing in Saudi enterprises are: the lack of commitment of service providers of the contracts items, the problems of maintaining and sustaining the confidentiality and security of information, the potential loss of a company's secrets and intellectual property, the inability to retain professional expertise and maintain critical IS/IT skills and competences, insufficient qualification of some of the providers staff, the inability of service providers to respond and react to occasional and unexpected IS/IT problems, and the loss of control over quality and the timetable of IS/IT projects From a practical standpoint, manages and practitioners alike stand to gain from the findings of this study. The results of the paper enable them to better understand and evaluate the benefits and risks of IS/IT outsourcing, and to champion IS/IT development for business success in their organizations.